2018
DOI: 10.1186/s12884-018-1952-5
|View full text |Cite
|
Sign up to set email alerts
|

Iodine deficiency in pregnant women after the adoption of the new provincial standard for salt iodization in Zhejiang Province, China

Abstract: BackgroundZhejiang has achieved the goal of elimination of iodine deficiency disorders (IDD) via the implementation of universal salt iodization (USI) since 2011. Iodine content in household table salt decreased from the national standard (35 ppm) to the Zhejiang provincial standard (25 ppm) in 2012. It is crucial to periodically monitor iodine status in pregnant women because IDD in pregnancy have adverse effects on fetal neurodevelopment.MethodsWe carried out a cross-sectional study between April 2014 and Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
2
15
1
Order By: Relevance
“…Especially among those using adequately iodized table salt, 40•81 % of them were still identified as iodine deficient, indicating that there was still a proportion of pregnant women with iodine insufficient status in some areas of Chongqing. Our study found no significant association between UIC of pregnant women and different iodine content in household table salt, which is different from other studies (11,12) and could be explained by the following two reasons. First, research has shown that iodized salt contributes 63•50 % of food iodine, but 24•60 % of this iodine is lost in cooking (16) .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Especially among those using adequately iodized table salt, 40•81 % of them were still identified as iodine deficient, indicating that there was still a proportion of pregnant women with iodine insufficient status in some areas of Chongqing. Our study found no significant association between UIC of pregnant women and different iodine content in household table salt, which is different from other studies (11,12) and could be explained by the following two reasons. First, research has shown that iodized salt contributes 63•50 % of food iodine, but 24•60 % of this iodine is lost in cooking (16) .…”
Section: Discussioncontrasting
confidence: 99%
“…Compared with other research in different provinces of China, the overall median UIC of pregnant women in Chongqing (171•90 μg/l) obtained in the present study is lower than that of Henan Province (204•20 μg/l in 2013 and 202•50 μg/l in 2014), but higher than in Zhejiang (130•47 μg/l) and Fujian Provinces (136•60 μg/l of Xiamen city), which did not meet the requirement level recommended by the WHO (14) . Zhejiang and Fujian had adopted the new provincial standard for iodized salt of 25 mg/kg in 2012 and then found pregnant women overall were iodine deficient in the following years (1,12) . Inadequate iodine intake in the two coastal provinces may be related to their lower provincial standard of iodized table salt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical analyses of food, excreta and serum for iodine and other chemical compounds were carried out at the Central Laboratory of Preventive Medicine in Tianjin Medical University using nationally standardised and validated methods. The contents of dietary iodine and faecal iodine (25) were determined using As-Ce catalytic spectrophotometry (2,26,27) . Specimens were blindly measured in duplicate.…”
Section: Laboratory Analysismentioning
confidence: 99%
“…The IUC dosing method used in this study was the Sandell-Kolthoff reaction in a single sample. Thus, it is important to emphasize that this iodine deficiency in Table-4 However, even with these measures, urinary iodine was still identified below the ideal in coastal populations (107.54μg/l), through the catalytic spectrophotometry of arsenic-which suggests that measures of iodine supplementation in this population should be evaluated [21]. A study conducted in Europe with 36 pregnant women identified a high frequency of iodine deficiency (83%) even in the 150μg iodine supplementation regimen in the prenatal and postpartum periods [22].…”
Section: Discussionmentioning
confidence: 99%